IMPLEMENTASI METODE PROTOTYPE PADA PEMBUATAN WEBSITE DESTINATION BRANDING PARIWISATA “PANTAITELUKAWUR.ID” DI DESA TELUK AWUR - Kurniawan, Indra; Ulfah, Sofia; Sholikah, Mar’atus; Mubais, Ahmad; Ayu Ramadhani, Nandha; Muhaimin, Muhammad (Universitas Islam Nahdlatul Ulama Jepara, 2024)
One area that has great tourism potential is Jepara Regency. Jepara is known for its natural beauty, especially its stunning beaches with white sand. Currently, tourists tend to search for information via the internet. The availability of easily accessible information is an important factor influencing the number of visits. However, Teluk Awur Beach is still not optimal in terms of branding and promotion. Research on the Implementation of the Prototype Method in Creating a Tourism Destination Branding Website